Konsep Perancangan Koridor Berbatas Pagar Perumahan Skala Besar Studi Kasus Koridor Selatan Kejawan Putih Tambak Surabaya - Nugrahini, Fibria Conytin (EMARA Indonesian Journal of Architecture, 2016)
City corridor with large scale housing fences bounded tends to decrease the road physical condition and it surrounding. This condition partly cause by uncontrolled informal activities which utilizing the fences without any authority to control. The aim of this study is to propose a design concept in a city corridor with large scale housing fences bounded, which located at Kejawan Putih Tambak southside corridor bounded with Pakuwon City residence of Surabaya. The main problem in Kejawan Putih Tambak southside corridor were uncontrolled supporting activities, a quite severe puddles, road damages, sharp roadturn, lack of environment cleanliness, temporary waste disposals activities along the roadside also have impacts on the corridor quality. Based on field observation, an analysis were conducted to establish a pre-design concept Â Â base analysis and factual synthesis, the 10 San Francisco urban design plan principles and Smardon theory. The pre-design concept was directional discussed with the residents and the road users in order to create the final corridor design concept. The design concept were visualized in the form of sketches, which are expected become a contibuted input for the stakeholders of Kejawan Putih Tambak southside corridor.